Evaluacion del contenido de carotenoides totales en cascaras de algunas variedades de naranjas venezolanas - Moreno Alvarez, M.J.=700 1 Belen, D.R.; Garcia, D.; Mendoza, L.
(Es, En)
Ilus., 29 ref.
Keywords: CITRUS SINENSIS; NARANJA DULCE; CAROTENOIDES; EXTRACTOS VEGETALES; SOLVENTES; VENEZUELA; EXTRACCION; SOLVENTES ORGANICOS